Group-based trajectory and predictors of anxiety and depression among Chinese breast cancer patients - Li, Wengao; Zhang, Qiongxiao; Xu, Yining; Sun, Hengwen; Wen, Youlu; Xu, Wenjing; Tong, Yiling; Garg, Samradhvi; Chen, Yu; Yang, Yuan (Frontiers in Public Health, 2022)
Background: The aim of the current study is to investigate the change in anxiety and depression amongst Chinese breast cancer patients and to identify causal associations between baseline variables and the trajectory of anxiety and depression within this identified group. Methods: This is a longitudinal prospective study. Three hundred women with breast cancer were recruited. Patient’s depression and anxiety were repeatedly measured by PHQ-9 and GAD-7 at baseline, 6 months, 12 months, and 18 months after discharge. The SAS 9.4 PROC Traj procedure was used to examine the group-based trajectory of these recruited patients. Linear mixed models (LMM) were utilized to examine anxiety/depression changes over time, accounting for relevant baseline demographic and clinical factors. Results: About 26.3% of the participants reported none or very mild anxiety over time, 60.7% reported stable low-level anxiety, and the remaining 13.0% showed significantly decreasing trend in GAD total scores. Meanwhile, 10.7% of the participants reported none or very mild depressive symptoms over time, 66.0% reported stable PHQ total scores throughout the research period, and 23.3% were classified as the ‘high level-decreasing group’. Patients reported significantly higher anxiety and depression scores in the first three assessments. Participants with no or mild life stress along with a positive personality tended to report lower anxiety and depression scores over time. Conclusion: Most of the breast cancer patients reported stable low-level anxiety and depression 18 months after discharge. Early assessment of optimism and stress levels among cancer patients might help identify people at risk of experiencing long-term anxiety and depression.